Challenges of Integrating Digital Innovation Strategies in Educational Technology to Enhance E-Government Implementation - Revaldhi, Andriana; Gaffar, Vanessa; Sofia, Alfira (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to identify the main challenges in integrating digital technology in education and e-government in Indonesia. The research method uses a literature approach to collect and analyze relevant literature on digital innovation in educational technology and e-government in Indonesia. Primary sources include scientific articles, theory books, government policy documents, and international journals to compare technology implementations in developing countries. This approach enriches the analysis with various theoretical perspectives and valid information on the challenges and solutions of digital implementation in the education and government sectors. The work identifies key challenges in integrating digital technologies for e-government and education, such as uneven infrastructure, low digital literacy, and resistance to change. The digital divide in 3T areas exacerbates inequality in access to education and public services. Potential solutions include infrastructure development, digital literacy training, master plan development, and public awareness campaigns. With collaboration between the government, the education sector, and the community, Indonesia can utilize digital technology to improve the quality of public services and socio-economic life.